Proust, Bakhtin, and the Dialogic Albertine: Voice and Fragmentation in The Captive - Jesse Kavadlo (Studies in 20th & 21st Century Literature, 2000)
This article provides a Bakhtinian reading of Proust's The Captive, the fourth novel of In Search of Lost Time, while at the same time it demonstrates how several of Bakhtin's key terms come to life in Proust's modern, self-conscious novel in a striking way. In particular, the character of Albertine is a fully Bakhtinian figure in the novel: she is at once intertextual (tied to photography and film), chronotopic (scattered through time and space as a living embodiment of narrative), and dialogic (many Albertines in a series). Proust's narrator's fragmentation of consciousness, particularly with regard to Albertine, as well as the novel's multiple voices and discourses, create a strong intertextual link between the two writers and their works.
Keywords: Bakhtinian reading; Proust; The Captive; In Search of Lost Time; Bakhtin; intertextual; photography; film; chronotopic; time; space; narrative; dialogic; Albertines; fragmentation of consciousness